Out door Class in Geometry Cal Polytechnic School San Luis Obispo, Cal. Feb. 4, 1910 - Frank Aston::::::photographer::: (1910)
Outdoor class in Geometry Feb. 4, 1910.' Male and female students, working in groups of four, some with books in hand some holding [rulers?] at angle to the ground. Girls in separate group from boys.